Implementasi Good Corporate Governance pada Badan Usaha Milik Desa - Aminullah Aminullah; Nur Rohmad Nuzil (Universitas Yudharta Pasuruan, 2022)
English Version Management and supervision of the sustainability of Village-owned enterprises can be carried out by various stakeholders including the general public. The application of good governance principles is the main key to a company's good reputation, both from an environmental, community or corporate point of view. the concept of Good Corporate Governance or GCG has several parts including Accountability, Fairness, Transparency, Independence, Responsibility, and Accountability. The purpose of this study was to examine the application of GCG principles to BumDes in Karangjati Village, Pandaan District, besides that this study also aimed to determine the level of trust in the community towards the management process carried out by BumDes and Village Government. This type of descriptive qualitative research is used in this study. From the research conducted, it was found that BumDes Karangjati has already implemented the principles of good governance, but the maximization of the implementation of the concept has not been maximized further, the development required requires an increase in human resources for BumDes Management as well as an increase in the role of Bumdes partners in order to realize an advanced and transparent Bumdes Versi IndonesiaPengelolaan dan pengawasan pada keberlanjutan badan usaha milik Desa dapat dilakukan oleh berbagai stakeholder termasuk masyarakat umum, Penerapan prinsip tata kelola yang baik menjadi kunci utama reputasi baik perusahaan, baik dari sisi lingkungan, masyarakat atau perusahaan. konsep Good Corporate Governance atau GCG memiliki beberapa bagian antaralain Accountability, Fairness, Transparency, Independency, Responsibility, dan Accountability. Tujuan pada penelitian ini adalah untuk mengkaji Penerapan Prinsip GCG pada BumDes di Desa Karangjati Kecamatan Pandaan, selain itu penelitian ini juga bertujuan untuk mengetahui tingkatan kepercayaan pada masyarakat terhadap proses pengelola yang dilakukan oleh BumDes dan Pemerintahan Desa. Jenis penelitian kualitatif deskriptif digunakan dalam penelitian ini. Dari penelitian yang dilakukan, ditemukan hasil bahwa BumDes Karangjati sudah menerapkan prinsip tatakelola yang baik, akan tetapi maksimalisasi dari implementasi konsep tersebut belum maksimal selanjutnya, pengembangan yang dibutuhkan dibutuhkan peningkatan SDM Pengurus BumDes sekaligus peningkatan peran mitra Bumdes demi terwujudnya Bumdes yang maju dan transparan